Glucose and glutamine availability regulate HepG2 transcriptional responses to low oxygen - Lai, Alvina G. (Wellcome Open Res, 2018)
Background: Little is known about the impact of nutrients on cellular transcriptional responses, especially in face of environmental stressors such as oxygen deprivation. Hypoxia-inducible factors (HIF) coordinate the expression of genes essential for adaptation to oxygen-deprived environments. A second family of oxygen-sensing genes known as the alpha-ketoglutarate-dependent dioxygenases are also implicated in oxygen homeostasis and epigenetic regulation. The relationship between nutritional status and cellular response to hypoxia is understudied. In vitro cell culture systems frequently propagate cells in media that contains excess nutrients, and this may directly influence transcriptional response in hypoxia. Methods: We studied the effect of glucose and glutamine concentration on HepG2 hepatoma transcriptional response to low oxygen and expression of hypoxia inducible factor-1α (HIF-1α). Mass spectrometry confirmed low oxygen perturbation of dioxygenase transcripts resulted in changes in DNA methylation. Results: Under normoxic conditions, we observed a significant upregulation of both HIF-target genes and oxygen-dependent dioxygenases in HepG2 cells cultured with physiological levels of glucose or glutamine relative to regular DMEM media, demonstrating that excess glutamine/glucose can mask changes in gene expression. Under hypoxic conditions, CA9 was the most upregulated gene in physiological glutamine media while TETs and FTO dioxygenases were downregulated in physiological glucose. Hypoxic regulation of these transcripts did not associate with changes in HIF-1α protein expression. Downregulation of TETs suggests a potential for epigenetic modulation. Mass-spectrometry quantification of modified DNA bases confirmed our transcript data. Hypoxia resulted in decreased DNA hydroxymethylation, which correlated with TETs downregulation. Additionally, we observed that TET2 expression was significantly downregulated in patients with hepatocellular carcinoma, suggesting that tumour hypoxia may deregulate TET2 expression resulting in global changes in DNA hydroxymethylation.   Conclusion: Given the dramatic effects of nutrient availability on gene expression, future in vitro experiments should be aware of how excess levels of glutamine and glucose may perturb transcriptional responses.